Anticoagulant Response to Agkistrodon Contortrix Venom (ACV test): a New Global Test to Screen for Defects in the Anticoagulant Protein C Pathway - Robert, A; Eschwège, V; Hameg, H; Drouet, L; Aillaud, M-F (Thrombosis and Haemostasis, 1996)
As specific assays used to identify defects in the protein C (PC) anticoagulant pathway are laborious and expensive, we describe here a global test to screen for these defects. This assay is expressed as the ratio of two activated partial thomboplastin times, one in the absence and one in the presence of 0,125 U/ml of the PC activator of Agkistrodon contortrix venom (ACV). Eight of the 168 healthy volunteers of the control group exhibited an ACV ratio below the lower normal limit of 3.37 [6 subjects with the mutation Arg 506 to Gin in their factor V gene (FV R506Q) and one with PS deficiency]. 128 patients who have had at least one episode of deep-vein thrombosis were retrospectively studied. All patients carrying FV Q506R (n = 48), PC deficiency (n = 14) or combined defects, i. e. FV Q506R and PC deficiency (n = 4) or FV Q506R and PS deficiency (n = 3), had ACV ratios < 3.37. PS deficient plasmas (n = 20) exhibited ACV ratios which overlapped normal range. ACV ratios of one out of seven patients with antithrombin deficiency, and 10% of patients without identified defect in the PC anticoagulant pathway (n = 30) were < 3.37. An ACV ratio raised to 3.70 could lead to a test identifying all patients with a defect in the PC anticoagulant pathway.